“BAKSO BOSS”: Evaluating the Impact of Serious Games Using GDLC and FFFL-HS for Small and Medium Enterprises (SMEs) - Ramdhan, Dimas; Bramanta Pandya Wisesa, Gede (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
Small and Medium Enterprises (SMEs) are fundamental to economic growth, substantially aiding employment and income generation. Many SMEs face sustainability issues from deficient management and limited financial literacy, particularly in Indonesia (where they form ~99% of businesses and 95% of employment). Financial literacy—making informed financial decisions —is crucial for owners to manage resources and improve outcomes effectively. This study addresses this critical gap by evaluating the impact of "Bakso Boss," a serious game developed to enhance financial knowledge and business management capabilities among beginner entrepreneurs. The game, which simulates food business management scenarios to replicate typical challenges faced by small enterprises, was created using the structured Game Development Life Cycle (GDLC) method. Its effectiveness was rigorously assessed through pre- and post-tests administered to 30 respondents aged 16-30 in Jakarta who were either new or aspiring SME owners, utilizing the Financial Fitness for Life: High School (FFFL-HS) questionnaire. Data analysis using the Wilcoxon Signed Rank Test revealed statistically significant improvements (p<0.01) across all assessed variables: General Financial Attitudes, Financial Self-Efficacy, Perceived Financial Behavioral Control, Financial Autonomy, and Financial Satisfaction. These findings strongly suggest that "Bakso Boss" effectively improves these essential skills in aspiring entrepreneurs. By linking game mechanics directly to real-world financial behaviors, "Bakso Boss" improved test scores and equipped participants with practical, applicable skills. Future iterations could expand scenarios by including digital payment systems to reflect evolving SME challenges, thereby further enhancing the game's relevance and applicability in fostering SME development.